Phytoplankton photophysiology across tropical eddies: Deconvolving nutrient, light, and community signals - Liu, Haoran; Xie, Yuyuan; Browning, Thomas J.; Xu, Feipeng; Huang, Bangqin (Frontiers in Marine Science, 2022)
Fast repetition rate fluorometry (FRRf) based on active chlorophyll fluorescence is a powerful, noninvasive tool for studying phytoplankton physiological status at high spatial and temporal resolution. The South China Sea (SCS) is one of the largest tropical–subtropical marginal seas in the world, which plays an important role in modulating regional carbon budget and climate. In this study, underway in situ FRRf measurements were carried out throughout the outer continental shelf of the northern SCS, the basin of the northern SCS, the cyclonic eddy influenced domain in the western SCS, and the basin of the southeastern SCS. Pronounced diurnal variability of FRRf-derived parameters were observed, characterized by a large midday depression and slight nocturnal depression of the maximum quantum yield of photosystem II (Fv/Fm) and a slight increase in the functional absorption cross-section of photosystem II photochemistry (σPSII) at noon. Fv/Fm at the surface was typically as low as 0.1–0.3 and exhibited higher values (~0.4) where internal waves occurred. The cyclonic eddy increased Fv/Fm slightly, implying that it had a limited impact on surface phytoplankton photophysiology. With proper interpretation, FRRf has been a powerful tool to assess the physiological status of phytoplankton in the sea and to correlate that to ocean dynamics in an unprecedented fine scale.